Structural Characterization of Lignin in Wild-Type versus COMT Down-Regulated Switchgrass - Ragauskas, Arthur; Pu, Yunqiao; Samuel, Reichel; Jiang, Nan; Fu, Chunxiang; Wang, Zeng-Yu (Frontiers in Energy Research, 2014)
This study examined the chemical structural characteristics of cellulolytic enzyme lignin isolated from switchgrass focusing on comparisons between wild-type control and caffeic acid 3-O-methyltransferase (COMT) down-regulated transgenic line. Nuclear magnetic resonance (NMR) techniques including 13C, 31P, and two-dimensional 13C-1H heteronuclear single quantum coherence (HSQC) as well as gel permeation chromatography (GPC) were employed. Compared to the wild-type, the COMT down-regulated transgenic switchgrass lignin demonstrated a decrease in syringyl (S): guaiacyl (G) ratio and p-coumarate:ferulate ratio, an increase in relative abundance of phenylcoumaran unit, and a comparable content of total free phenolic OH groups along with formation of benzodioxane unit. In addition, COMT down-regulation had no significant effects on the lignin molecular weights during its biosynthesis process.